A non-luminescent Eu-MOF-based "turn-on" sensor towards an anthrax biomarker through single-crystal to single-crystal phase transition. Issue 99 (26th November 2019) - Wu, Dai; Zhang, Zhe; Chen, Xiwen; Meng, Lingkun; Li, Chunguang; Li, Guanghua; Chen, Xiaobo; Shi, Zhan; Feng, Shouhua
Abstract : A non-luminescent NH2 -MOF-76(Eu) exhibits selective fluorescence recovery for sensing anthrax biomarker DPA through a single-crystal to single-crystal phase transition. Abstract : A porous NH2 -MOF-76(Eu) (MOF 1 ) with unexpected non-luminescence was designed and synthesized. It exhibits selective fluorescence recovery for sensing dipicolinic acid (DPA), a biomarker of Bacillus anthracis . Moreover, a new europium-based MOF (MOF 2 ) with evident channel changes was obtained through a single-crystal to single-crystal phase transition.